Social-Emotional Learning For Post-Secondary Success - Collier, Gena (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Integrating social-emotional learning into High School English Language Arts supports growth in the emotional intelligence of students which is needed for post-secondary success. Social-emotional learning develops student competence in self and social awareness, reasonable decision making, establishing relationships, and self-management. These competencies improve students’ academic achievement and attitude about school. This can be critical to their transition and adjustment to postsecondary life as they enter college and the workplace. As students become employees, there is an expectation that they will be able to conduct themselves professionally and perform well in their jobs or careers. Postsecondary success is a main goal of schooling, so learning how to integrate social-emotional learning into high school English language arts is worthwhile.